Barriers, Enablers, and Consumer Design Ideas for Health Literacy Responsive Hospital Waiting Areas: A Framework Method Analysis. (January 2022) - McDonald, Cassie E.; Remedios, Louisa J.; Cameron, Kate L.; Said, Catherine M.; Granger, Catherine L.
Aim: The study aim was to (1) investigate the barriers and enablers experienced by consumers to accessing and engaging with health tools in hospital waiting areas and (2) evaluate consumers' ideas for designing a health literacy responsive waiting area. Background: Health information, resources, and supports ("health tools") in waiting areas should be responsive to the health literacy needs of consumers. However, consumers' experiences of using health tools and their ideas for improving them are not known. Methods: Multicenter study was set in hospital waiting areas of outpatient rehabilitation services. Semistructured in-person interviews were conducted with 33 adult consumers attending appointments for various health conditions. Seven stages of the Framework Method were used to analyze data. Results: Six themes were identified which explained barriers and enablers from the perspective of consumers. The barriers were accessibility issues; personal factors—physical condition, emotional state, and preferences; and poorly presented and outdated resources. The enablers were design suits consumer needs and preferences; usable in available time or portable; and compatible environment for engaging and sharing. Consumers shared design ideas which fit within four typologies. Conclusions: A range of barriers and enablers exist which have an impact on consumers' ability to engage with available health information, resources, and supports in hospital outpatient waiting areas. Practical insights from the perspective of consumers can be applied to future health service design. Consumer's design ideas suggest that partnerships with consumers should be formed to design health literacy responsive waiting areas.